2011
DOI: 10.5812/aapm.1337
|View full text |Cite
|
Sign up to set email alerts
|

Premedication with oral clonidine decreases intraoperative bleeding and provides hemodynamic stability in cesarean section

Abstract: Background: Intentional lowering of blood pressure helps to produce a desirably clean surgical field. Many drugs can be used to induce a hypotensive state, but due to their high potency and rapid effect, drugs that more easily and safely control the induction of hypotension are desirable. Objectives: To investigate the effects of premedication with oral clonidine on intraoperative bleeding and hemodynamic variables in patients undergoing cesarean sections. Patients and Methods: A total of 110 patients classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…So prior to laryngoscopy, additional pharmacological measures like use of volatile anaesthetics, topical and intravenous lidocaine, opioids, vasodilators-SNP, NTG, Calcium channel blockers and β-blockers have been tried but none was found ideal. [3,4] Clonidine, a central α-2 agonist has sedative, analgesic and antihypertensive actions. [5] Hence, there is a need to study the effects of intravenous clonidine for attenuation of hemodynamic stress response to laryngoscopy and intubation.…”
Section: Introductionmentioning
confidence: 99%
“…So prior to laryngoscopy, additional pharmacological measures like use of volatile anaesthetics, topical and intravenous lidocaine, opioids, vasodilators-SNP, NTG, Calcium channel blockers and β-blockers have been tried but none was found ideal. [3,4] Clonidine, a central α-2 agonist has sedative, analgesic and antihypertensive actions. [5] Hence, there is a need to study the effects of intravenous clonidine for attenuation of hemodynamic stress response to laryngoscopy and intubation.…”
Section: Introductionmentioning
confidence: 99%
“…The general idea in many studies is based on that general anesthesia with propofol provides better vision of surgical field and less amount of hemorrhage during the operation compared to Isoflurane or Sevoflurane ( 5 ). A group of studies suggest that premedication with oral clonidine decreases intraoperative bleeding in some surgeries ( 6 , 7 ). Metoprolol has shown to decrease bleeding in nasal sinuses ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these advantages of SA, decreasing blood loss is a main issue of SA in PCNL surgery. Recent studies investigated the effects of a 200-μg of oral clonidine tablet 60 -90 minutes before anaesthesia, which reduced blood loss significantly in several kinds of surgeries under GA that could be a future choice along with SA in PCNL [24,25] Tetzlaff et al have also shown that in spinal surgeries, SA was a better choice for anaesthesia compared to GA resulting in lower side effects [26].…”
Section: Discussionmentioning
confidence: 99%